New Universities’ Organizational Identities Through Presidential Lenses - Levin, John S.; López Damián, Ariadna I.; Martin, Marie C.; Vázquez, Evelyn M. (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2018)
This qualitative investigation addresses three new universities in the provinces of British Columbia and Alberta and their presidents’ ascriptions of organizational identity to their universities. Through extended, semi-structured interviews and narrative analysis, this investigation uses organizational identity theory and institutional theory to explain the positionality and understandings of presidents in relationship to their universities’ paths to legitimacy. We found that the preservation of aspects of the institutions’ original identity (as community colleges) aids new universities’ organizational change. Furthermore, while presidents advocated for a replacement of community college logics with university logics, data showed that these three new universities had yet to embrace the university logic fully. We propose that a blending of logics may be the preferred mechanism for the attainment of legitimacy during sectoral change for new universities.This qualitative investigation addresses three new universities in the provinces of British Columbia and Alberta and their presidents’ ascriptions of organizational identity to their universities. Through extended, semi-structured interviews and narrative analysis, this investigation uses organizational identity theory and institutional theory to explain the positionality and understandings of presidents in relationship to their universities’ paths to legitimacy. We found that the preservation of aspects of the institutions’ original identity (as community colleges) aids new universities’ organizational change. Furthermore, while presidents advocated for a replacement of community college logics with university logics, data showed that these three new universities had yet to embrace the university logic fully. We propose that a blending of logics may be the preferred mechanism for the attainment of legitimacy during sectoral change for new universities.